Experiencing God in everything and nothingness negativity, embodiment, and spirituality - South African perspectives - Potgieter, Annette; Delport, Khegan (Eugene, Oregon Pickwick Publications, 2024)
"COVID-19 has impacted the way we see the world and the way we view spirituality; in times of crisis, people turn or return to religion or spirituality. Most of the South African population identifies as Christian. This brings to the fore what is meant by "spirituality" in a country crippled by the remains of apartheid structure, rampant corruption, poverty, and various systemic problems. Overall, there is a lack of scholarship investigating "spirituality" and "spirituality studies" from the global South. This book aims to bridge the gap. New avenues are investigated of thinking about God in difficult circumstances, as ideologies of hope and prosperity are reshaped. This book links text and context, spirituality and material culture, self and society, the analogue and the digital, contemplation and action, saying and unsaying; in short, the question of experiencing God in both everything and nothingness comes under the scope of this book."--
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Spiritual Life; Spiritual Life -- Christianity -- History of doctrines; Christian Life -- South Africa; Vie chrétienne - Afrique du Sud; Aufsatzsammlung